Representation of History in Longer Slovenian Youth Fiction: From the Narrative Invention of Tradition Towards the Promotion of Intercultural Dialogue and Critical Thinking (Preučevanje otroške in mladinske književnosti, 2025)
The paper examines the development of Slovenian youth historical fiction. Interpreting its proto-texts by Finžgar and Jalen I refer to the concepts of invented tradition (Hobsbawm) and the coexistence of various forms of cultural remembrance (Rigney). Historical Slovenian fiction (which has been appropriated for the young readers) used historical sources to create a narrative framework of invented tradition appropriated by an emerging national community whose cultural remembrance had previously been supressed due to political subordination. The invented narrative framework of tradition presented the Slavic tribes as heroic, sovereign peoples and it used the idea of the ancestral continuity to promote patriotic pride. Contemporary historical youth fiction by Karlovšek and Pregelj refers to these proto-texts, supplementing their patriotic tradition with the recent archaeological findings, by critical reflection on historical practices and by intercultural dialogue.